1977
DOI: 10.1111/j.1399-3054.1977.tb09277.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Synchronization of Carrot Cell Culture by Auxin Deprivation

Abstract: A strain of carrot cells (Daucus carota cv. Kintoki) grew exponentially in the presence of 2,4‐dichlorophenoxyacetic acid (2,4‐D, 1 mg/1) with a doubling time of about 2 days. When those cells were transferred to a medium lacking 2,4‐D, they continued to grow at almost the same rate for about a week. When the cells were again transferred to the auxin‐free medium, the rate of cell division gradually decreased. After the cell division had ceased, cells were returned to the ordinary 2,4‐D medium. A burst of cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…In cultured carrot cells, temporary auxin deprivation induces at least partial synchronization of cell division (NISHI et al 1977), a response not shown by cultured tobacco cells. Cell arrest during auxin deprivation appears to be in G l' suggesting that auxin is needed to initiate the S phase of the cycle.…”
Section: Effect Of Auxinsmentioning
confidence: 98%
“…In cultured carrot cells, temporary auxin deprivation induces at least partial synchronization of cell division (NISHI et al 1977), a response not shown by cultured tobacco cells. Cell arrest during auxin deprivation appears to be in G l' suggesting that auxin is needed to initiate the S phase of the cycle.…”
Section: Effect Of Auxinsmentioning
confidence: 98%
“…The cessation of cell divisions upon a second culture in a 2,4-D deficient medium is probably linked to the decrease of levels of active forms of 2,4-D [29] and the quiescence is probably due to an arrest of the cell cycle at the G1 phase as previously demonstrated in carrot cells [12]. A renewal of cell divisions occurred when the cells were transferred to the standard medium supplemented by 2.3/tM or 4.5/~M or 6.8 #M of 2,4-D, suggesting that these 2,4-D concentrations are over the threshold value required for division [13] which is not the case for the concentration of 0.45 #M 2,4-D.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 66%
“…The first hypothesis would be more plausible. Nishi et al [12] have demonstrated in carrot cultures that 2,4-D deprivation synchronizes cell divisions. In the experiment described here, it could be that during starvation, the cells had been arrested at the G1 phase.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows that absence of 2,4-D resulted in the arrest of cells in the G~ phase exclusively, and that the addition of 2,4-D induced the synchronized synthesis of DNA and subsequent division of cells. This system seems to be better in the terms of the degree of synchronization than previously reported similar systems (Nishi et al 1977). This system has the following advantages, i.e.…”
Section: Discussionmentioning
confidence: 69%